Opportunities and challenges of resident specialists' attendance plan guidelines (health-care transformation plan) in Isfahan university hospitals in 2015 - Reza Moradi; Saeid Karimi; Mohammad Hossein Yarmohammadian; Mohammad Zakaria Kiaei; Elaheh Mazaheri (Wolters Kluwer Medknow Publications, 2018)
Background: Given new reforms in Iran's health-care system and due to the need for gathering evidence regarding the implementation of this plan, this study aimed to investigate opportunities and challenges created by resident specialist attendance plan guidelines in university hospitals. Materials and Methods: This study used the qualitative method. Semi-structured interviews were used for data gathering. The study population included all experts of Isfahan University of Medical Science. Sampling was carried out using purposeful sampling method and continued until data saturation was reached. In total, 16 experts were interviewed. Criteria such as "reliability of information," "trustworthiness," and "verifiability of the information" were considered. Interviewees were assured that their names would keep hidden and that all information is confidential. Subject analysis method was used for data analysis. Results: The findings of this study based on subject analysis led to extracting three themes in regards of challenges in the implementation of resident (specialist or fellowship) plan in hospitals including structural, management, and resource challenges and one theme in the area of opportunities which were improved quality and timely provision of services. Conclusion: The findings showed that despite the strengths of this guideline, there are some fundamental challenges in various areas and need better attention by national level policymakers. These results help health-care policymakers to evaluate the problem with a better attitude and improve the necessary plans for implementation of these guidelines.